The treaty prohibiting nuclear weapons : legal challenges for military doctrines and deterrence policies / Jonathan L. Black-Branch. - Black-Branch, Jonathan L. (Cambridge University Press, 2021)
The Treaty on the Prohibition of Nuclear Weapons (2017) sets out to challenge deterrence policies and military defence doctrines, taking a humanitarian approach intended to disrupt the nuclear status quo. States with nuclear weapons oppose its very existence, neither participating in its development nor adopting its final text. Civil society groups seem determined, however, to stigmatize and delegitimize nuclear weapons towards their abolition. This book analyzes how the Treaty influences the international security architecture, examining legal, institutional and diplomatic implications of the Treaty and exploring its real and potential impact for both states acceding to the Treaty and those opposing it. It concludes with practical recommendations for international lawyers and policymakers regarding non-proliferation and disarmament matters, ultimately noting that nuclear weapons threaten peace, and everyone should have the right to nuclear peace and freedom from nuclear fear.